Analisis Peningkatan Kualitas Pelayanan Kesehatan Terhadap Kepuasan Pasien Menggunakan Importance Performance Analysis dan Metode Quality Function Deployment - Thabrani, Gesit; Firman, Firman; Azmi, Nia Lailatul (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2017)
Competition increasingly competitive requires every company both manufacturing and services, including RSUD Pariaman to always consider the customer wants and needs and try to meet what they expect. The purpose of this research is to analyze how is the quality of service, a service attribute be the first priority, and recommendations can be given to improve the quality of services RSUD Pariaman. The results showed that 25 of the 26 attributes of service is worth the negative gap with the largest value of -1.21 for the attribute